Postmemory and migration in contemporary multilingual literature by Tomer Gardi, Katja Petrowskaja and Igiaba Scego - Vlasta, Sandra (Transnational 20th Century. Literatures, arts and cultures, 2022)
Contemporary multilingual writing often reveals and works through collective memory and trauma inscribed in language, such as the Shoah, wartime atrocities, colonialism, genocide, exile and migration. Often composed by members of the second or third generation, these texts can be considered postmemory narratives (Marianne Hirsch). In this contribution, I scrutinise how these texts, with their particular multilingual poetics, question official memory discourses and offer an alternative perspective, often that of underprivileged subjects such as immigrants, guest workers and former colonial subjects. My comparative analysis focuses on texts by Tomer Gardi, Katja Petrowskaja and Igiaba Scego. In my study, I am particularly interested in the nexus of language, migration, multilingualism and memory that is suggested in the texts and that offers a starting point for the negotiation of new, inclusive concepts of belonging.